Implementation of Naive Bayes Classifier and Log Probabilistic for Book Classification Based on the Title - Rismanto, Ridwan; Wahyu Wibowo, Dimas; Rachmad Syulistyo, Arie (International Journal of Engineering and Technology, 2018)
Book is an important medium for teaching in higher education. It is facilitated by a library or a reading room which enabled student and teacher to fulfill their references for teaching and learning activities. For easy searching, each book classified by categories. In our institution, Information Technology Major of State Polytechnic of Malang, those categories are specifics to computer science topics. Every book entry need to be classified accordingly and to perform such task, one need to understand major keywords of the book title to correctly classify the books. The problem is, not all the librarian have such knowledge. Therefore manually classifying hundreds and even thousands of book is an exhausting work. This research is focused on automatic book classification based on its title using Naive Bayes Classifier and Log Probabilistic. The Log Probabilistic implementation is to solve the probability calculation result that is too small that cannot be represented in a computer programming floating points variable type. The algorithm then implemented in a web application using PHP and MySQL database. Evaluation has been done using Holdout method for 240 training dataset and 80 testing dataset resulting in 75% of accuration. We also tested the accuracy using K-fold Cross Validation resulting in 66.25% of accuration.Â Â